(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article delves into the fascinating realm of language universals, elucidating the fundamental principles that underpin the structure and function of diverse human languages. The piece meticulously examines various facets of language, including phonology, grammar, semantics, and pragmatics, highlighting the recurring patterns and characteristics observed across linguistic systems worldwide. The article systematically presents an overview of linguistic universals, expounding on their significance in understanding the innate aspects of human language acquisition and use. It navigates through theories such as the innateness hypothesis and cultural evolution, offering a nuanced exploration of how these theories contribute to elucidating the origins and existence of language universals.